Isolation, screening and selection of xylanase producing thermophilic fungi from Raipur - PARIHAR, PREETI SINGH (Research in Biotechnology, 2015)
In the present study, isolation, screening and selection of xylanase producing thermophilic fungi from soil of Raipur was studied. A total of 55 fungal isolates were isolated and screenedÃ‚Â forÃ‚Â xylanaseÃ‚Â activityÃ‚Â byÃ‚Â standardÃ‚Â plate assay method and activity of xylanase was determined by estimating the amount of releasedÃ‚Â reducingÃ‚Â sugarÃ‚Â xyloseÃ‚Â inÃ‚Â cultureÃ‚Â filtrates. Based on screening methods, 18 isolates with higher xylanase activity were selected for studying effect of temperature i.e.Ã‚Â 25,Ã‚Â 35,Ã‚Â 45,Ã‚Â 50,Ã‚Â 55,Ã‚Â 60,Ã‚Â 65oC on their mycelial biomass production andÃ‚Â for studying percentÃ‚Â coagulationÃ‚Â of proteinÃ‚Â at 50oCÃ‚Â atÃ‚Â differentÃ‚Â intervalsÃ‚Â ofÃ‚Â time. Five isolates namely Chrysosporium tropicum NFCCI 2531, MalbrancheaÃ‚Â cinnamomea MTCCÃ‚Â 11894,Ã‚Â AspergillusÃ‚Â fumigatus NFCCIÃ‚Â 2532, AspergillusÃ‚Â terrus NFCCIÃ‚Â 2533Ã‚Â andÃ‚Â EmericellaÃ‚Â nidulans NFCCI2538Ã‚Â showed maximum biomass productionÃ‚Â at 45oC (0.19 to 0.32g/100ml/10days)Ã‚Â and minimum protein coagulation at 50oC (14% to 25%). Keywords: Thermophilic fungi, screening, xylanase, temperature biomass, protein coagulation, reducing sugar, xylose. Ã‚Â